SHEAR STRENGTHENING AND REHABILITATING OF REINFORCED CONCRETE T-BEAMS USING EXTERNALLY CARBON FIBER REINFORCED POLYMER SHEETS - Beramly, Mervat; Abdel-Jaber, Mutasim; Katkhuda, Hasan; Shatarat, Nasim; Al-diseet, Malak (Journal of Applied Engineering Science, 2022)
The shear behavior of reinforced concrete (RC) T-beams using externally bonded carbon fiber-reinforced polymers (CFRPs) composites is investigated experimentally and theoretically in this research. Nine RC T-beams were cast and tested under monotonic one-point loading. The variables used in this study are: the situation of specimens (strengthened or rehabilitated); type of CFRPs material (laminate or sheet); and the CFRPs configuration (inclined or horizontal).  The experimental results were compared to theoretical results from nonlinear finite element (FE) models for T-beams using ABAQUS software. The experimental results showed that using different CFRPs materials in various configurations effectively improved shear capacity for strengthening and rehabilitating RC T-beams. Compared to the control beam, the three schemes used to strengthen the shear of RC T-beams were successful in increasing the maximum load capacity by a range of 13.6 to 36.4%, and by 4.6 to 27.3% for rehabilitate T-beams. The included horizontal strips of CFRPs laminates achieved the highest increase in the shear capacity for strengthened T-beams. While, for the rehabilitated T-beams the results showed that the CFRP scheme that included full wrap of the web with CFRPs sheets was the best. A good agreement was found between the experimental and theoretical results. The differences in the ultimate loads and mid-span deflections were in the range of 0.33% to 26%, and 0.32% to 6.6%, respectively.
Keywords: Т-beams, reinforced concrete, shear behavior, CFRP, experimental study, theoretical study